Taxonomic changes in the emerald moths (Lepidoptera: Geometridae, Geometrinae) of East Asia, with notes on the systematics and phylogeny of Hemitheini - Beljaev, Eugene A. (Zootaxa, 2007)
The following taxonomic changes in the East Asian Geometrinae are proposed: Jodis orientalis Wehrli, 1923, stat. n.; Jodis angulata Inoue, 1961, syn. n. of Jodis putata orientalis Wehrli, 1923; Aoshakuna Matsumura, 1925, stat. nov., from synonymy with Chlorissa Stephens, 1831; Nipponogelasma Inoue, 1946, syn. n. with Aoshakuna Matsumura, 1925; Aoshakuna sachalinensis Matsumura, 1925, syn. n. of Gelasma lucia Thierry-Mieg, 1916; Aoshakuna lucia (Thierry-Mieg, 1916), comb. n.; and Microloxia chlorissoides (Prout, 1912), comb. n. Aoshakuna lucia ussurica, ssp. n., is described from the continental part of East Asia. The tribal concept of Hemitheini and putative phylogenetic relationships among the genera related to Aoshakuna are discussed.